Impact of simplified chemical treatment of semi-direct restorations cemented with self-adhesive resin cement on dentin bond durability and nanoleakage (Research, Society and Development, 2020)
The present study aimed to evaluate the impact of different chemical surface treatments and aging on dentin bond strength and nanoleakage of semi-direct restorations cemented with self-adhesive resin cement. One hundred and sixty semi-direct composite restorations (4.8 x 2.8 x 4.0 mm) were produced to fill dentin preparations in bovine tooth, and the specimens were divided into 8 groups according to chemical treatment [No treatment, Silane (S), Scotchbond™ Universal adhesive (SBU), and S+SBU], and aging time in water [24 h and 6 months]. Push-out bond strength (PBS) was measured through a universal testing machine (1.0 mm/min), failure modes by a dissecting microscope, and nanoleakage by scanning electron microscopy. Two-way ANOVA and Tukey's post-hoc (p